Development of a Multiplex PCR Assay for the Detection of Tomato Wilt Caused by Coinfection of Fusarium brachygibbosum, Fusarium oxysporum, and Ralstonia solanacearum Based on Comparative Genomics - Liu, Jun (Plant disease, 2024)
Tomato is consumed worldwide as fresh or processed food products. However, soilborne diseases of tomato plants caused by coinfection of various pathogens result in great economic losses to the tomato industry. It is difficult to accurately identify and diagnose soilborne diseases of tomato plants caused by pathogen complexes. In this study, we investigated field diseases of tomato plants by pathogen isolation and molecular identification and found that tomato wilt was caused by coinfection of Fusarium brachygibbosum, F. oxysporum, and Ralstonia solanacearum. Therefore, developing a method for simultaneous detection of DNA from F. brachygibbosum, F. oxysporum, and R. solanacearum is of great importance to efficiently and accurately monitor disease development at different growth stages of tomato plants. In this study, we performed a comparative genomic analysis of F. brachygibbosum, F. oxysporum, and R. solanacearum and determined the primer sets for simultaneous detection of DNA from these target pathogens. Then, we tested the reagent and condition parameters of multiplex PCR, including primers, dNTP and Mg2+ concentrations, and annealing temperatures, to determine the optimal parameters of a multiplex PCR system. We evaluated the specificity, sensitivity, and stability of the multiplex PCR system based on the optimized reaction conditions. The multiplex PCR system can specifically identify 13 target pathogens from 57 different fungal and bacterial pathogens, at the lower detection limit of the three target pathogens at concentrations of 100 pg/μl. In addition, we can accurately identify the three pathogens in tomato plants using the optimized multiplex PCR method. These results demonstrated that the multiplex PCR method developed in this study can simultaneously detect DNA from F. brachygibbosum, F. oxysporum, and R. solanacearum in a single PCR system to accurately identify and diagnose the pathogen causing tomato wilt